Drug release from a surface erosion biodegradable viscoelastic polymeric platform: Analysis and numerical simulation. (15th December 2020) - Azhdari, E.; Emami, A.; Ferreira, J.A.
Abstract: In this paper, a system of partial differential equations, that can be used to describe the drug release from a biodegradable viscoelastic polymeric platform, is studied from an analytical and numerical point of view. The system is defined in a moving boundary domain and its stability is analysed. From numerical point of view, a numerical method is proposed and its convergence properties are established. In the context of the drug release from biodegradable polymeric platforms, the qualitative behaviour of the differential system is numerically illustrated.